Reaksi Pasar terhadap Perpindahan Ibu Kota Negara Republik Indonesia - Wahyudi Rumaday, Dicky; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p07, 2020)
This research is an event study that aims to determine the market reaction arising from the movement of the capital city of the Republic of Indonesia. The date chosen as the event date is April 29, 2019 when the issue first came out and August 26, 2019 when the official announcement. The samples used in this study are all companies included in the LQ45 index for the February-July 2019 and August 2019-January 2020 periods. The data analysis technique used is the different test. The results showed there were no differences in the average abnormal return before and after the issue first came out, but there were differences in the average abnormal return before and after the official announcement. There is a difference in the average trading volume activity before and after the issue first came out and when the official announcement of the move of the capital of the Republic of Indonesia. Keywords: Market Reaction; Abnormal Return; Trading Volume Activity; Capital Movement.